PERAN KELUARGA DALAM MENGAJARKAN AL-QUR’AN KEPADA ANAK SEJAK DINI - Umi Nasikhah; Herwani Herwani (Borneo : Journal of Islamic Studies, 2022)
Al-Qur'an is the word of Allah which was revealed to the Prophet Muhammad as a guide for mankind on earth. The Qur'an is the last book revealed by Allah swt as a source of Islamic law, a guide for human life to achieve prosperity in life in the world and the hereafter, including in caring for and nurturing children in order to get the highest degree before Allah swt. This study was conducted to examine how the role of the family, especially parents, teach the Qur'an to their children from an early age. The approach used is a qualitative approach, to construct reality, to understand what is hidden behind phenomena that are sometimes difficult to understand satisfactorily. The results of the study show that children's education is not only when they are born into the world, but begins when parents look for companions, while in the womb (prenatal), and after birth. Along with the development of technology and globalization, parents should always accompany, maintain and improve their children's ability to read and understand the content of the Qur'an. With the basic education that children have, it is hoped that they will be able to filter out the negative side brought by advances in technology and globalization today.